2021
DOI: 10.3390/s21103488
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Walker for People with Both Visual and Mobility Impairment

Abstract: In recent years, significant work has been done in technological enhancements for mobility aids (smart walkers). However, most of this work does not cover the millions of people who have both mobility and visual impairments. In this paper, we design and study four different configurations of smart walkers that are specifically targeted to the needs of this population. We investigated different sensing technologies (ultrasound-based, infrared depth cameras and RGB cameras with advanced computer vision processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Instead, they found that multiple and different choices of sensors can provide a similar user experience. Nevertheless, emphasis should be given to the fact that active sensors (ultrasonic distance sensors or infrared depth cameras) provide a better accuracy for the localization of objects/obstacles [1]. The authors also reach the conclusion that it is necessary to perform a holistic evaluation of the walker in terms of its end-to-end performance, and that the user interface is of big importance to the overall performance of a smart walker [1].…”
Section: Contributed Papersmentioning
confidence: 92%
See 1 more Smart Citation
“…Instead, they found that multiple and different choices of sensors can provide a similar user experience. Nevertheless, emphasis should be given to the fact that active sensors (ultrasonic distance sensors or infrared depth cameras) provide a better accuracy for the localization of objects/obstacles [1]. The authors also reach the conclusion that it is necessary to perform a holistic evaluation of the walker in terms of its end-to-end performance, and that the user interface is of big importance to the overall performance of a smart walker [1].…”
Section: Contributed Papersmentioning
confidence: 92%
“…The authors of [1] presented the design and study of different mobility aids (smart walker) configurations, targeting the population who suffers from visual and mobility Acknowledgments: M. Fátima Domingues acknowledges the REAct (FCT-IT-LA) scientific action.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Examples include meal-assistance robots [ 37 , 38 , 39 ], brain-computer interfaces controlling wearable robots [ 40 , 41 ], and robot-assisted therapy [ 42 , 43 ]. In this context, some researchers have proposed smart robotics walkers to sustain the mobility of elderly people, or with some motion disabilities [ 44 , 45 , 46 ]. Smart robotics walkers “intend to assist the mobility function of disabled people that present reduced lower motor function and low balance, by improving their autonomy” [ 47 ] by facilitating a stable gait and easy maneuverability.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…All these smart walkers are identified to consist of some controlling electronic devices, computing algorithms, sensors, and actuators [19]. The main focus of the researchers is to improve the device performance in terms of precise motion, which is hampered due to horizontal force on gait [20], reduced power consumption, additional safety features, and assisting capability for visually impaired users [21], automatic training of walkers, reduced vibration in smart walkers with optimization of electric circuitry of motors, and improving human-machine interaction for better coordination in controlling. In the past few decades, researchers have explored various control strategies for improving coordination in the human-machine interface-based smart walkers [22].…”
Section: Introductionmentioning
confidence: 99%